The effect of temperature on structure formation in three insect batters. (August 2019) - Scholliers, Jana; Steen, Liselot; Glorieux, Seline; Van de Walle, Davy; Dewettinck, Koen; Fraeye, Ilse
Abstract: Since insects are a promising alternative protein source, the application potential of three insect larvae ( Alphitobius diaperinus, Tenebrio molitor and Zophobas morio ) for food purposes was explored. To this end, the effect of isothermal heating at 5 different temperatures (70 °C–90 °C) on structure formation in insect batters was studied rheologically. Meat batters (with the same protein content as insect batters), isothermally heated at 70 °C, were also studied for comparison. Cryo-SEM imaging was used to visualize the microstructure of raw and heated insect batters. These images showed that a network was formed in the heated batters, as well as in the raw batters. However, no clear effect of temperature or insect larva on the microstructure was observed. Rheologically, both the heating temperature applied and the insect larva used were shown to have a significant effect on the viscoelastic properties of the insect batters. Generally, batters containing Z. morio larvae showed both higher storage moduli (G′) and longer linear viscoelastic regions (LVRs) compared to the other insect larvae, indicating that these larvae had the best structure forming capacities. Furthermore, both G' and the length of the LVR increased with increasing isothermal heating temperature, indicating more structure formation and structure stability in insect batters heated at higher temperatures. Compared to the meat batters, however, the insect larvae were shown to have inferior structure forming capacities. Even at the highest heating temperature (90 °C) the viscoelastic properties of the insect batters only approached those of meat batters heated at 70 °C. Therefore, it was concluded that higher heating temperatures may need to be employed in insect-based food products compared to meat products in order to obtain sufficient structure formation and the desired textural properties. Graphical abstract: Unlabelled Image Highlights: Structure formation in insect batters was studied through rheology and cryo-SEM. Increasing the heating temperature resulted in more structure formation. Of the insects studied, Zophobas morio had the best structure forming capacities. The structure forming capacities of the insects were inferior to those of meat.